SMARTI University Model and Performance Benchmarking System UPM - Nguyen, Huu Thanh Chung (H. : ĐHQGHN, 2020)
In the globalization context, Vietnamese higher education institutions need to fulfill the functions of the third generation university as well as the challenges of the fourth industrial revolution. In this case, the innovation-driven smart university, namely SMARTI model, was proposed. By the approach of the university ecosystem, SMARTI model has been described with 5 core values: digital skills and entrepreneurship; flexibility and connectivity; research and innovation; internationalization; and promotion of social norms. The SMARTI can be governed and benchmarked through the criteria of the university performance metrics (UPM). Preliminary implementations were employed for Vietnam's leading institutions. The results show that these universities have achieved a 5-star standard equivalent to excellent universities in the top 300 in Asia